2005
DOI: 10.1088/0963-0252/14/1/009
|View full text |Cite
|
Sign up to set email alerts
|

On NOxproduction and volatile organic compound removal in a pulsed microwave discharge in air

Abstract: The production of NO and NO 2 and the removal of 3-pentanone, as an example for volatile organic compounds (VOCs), in a pulsed microwave discharge in air, near atmospheric pressure has been studied. The influence of changing the pulse duration from 25 to 500 µs and of the pulse repetition rate from 10 to 500 Hz is reported. At a relatively high pressure of p = 800 mbar, plasma ignition is achieved by inserting BaTiO 3 pellets inside the microwave excitator. The concentrations of NO and NO 2 have been monitored… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 39 publications
(48 reference statements)
2
39
0
Order By: Relevance
“…Kuroki et al reported NOx formation problem from the decomposition of adsorbed xylene on zeolite using AC barrier discharge plasma in air [24]. Microwave (MW) plasma is also known to produce high concentration of NO and NO 2 (∼4000 ppm) when it is operated at air-like mixture [25]. The common factor for these two methods is high specific input energy up to several tens kJ L −1 .…”
Section: -P3mentioning
confidence: 99%
“…Kuroki et al reported NOx formation problem from the decomposition of adsorbed xylene on zeolite using AC barrier discharge plasma in air [24]. Microwave (MW) plasma is also known to produce high concentration of NO and NO 2 (∼4000 ppm) when it is operated at air-like mixture [25]. The common factor for these two methods is high specific input energy up to several tens kJ L −1 .…”
Section: -P3mentioning
confidence: 99%
“…Nevertheless, the ignition of the microwave plasma at atmospheric pressure is not as simple as with the DBD. In one setup the ignition of a microwave plasma is possible at a working pressure of 800 mbar with added BaTiO 3 pellets, which enhances the electric field strength at the edges of the pellets [71]. The pulsed microwave discharge is used for the decomposition of 200 ppm acetylene in air at 800 mbar.…”
Section: Pulsed Microwave Discharge Reactorsmentioning
confidence: 99%
“…Various precursor molecules like BCl 3 , BF 3 or B 2 H 6 are used to provide active boron-containing species in the plasmas. In particular Boron Trichloride (BCl 3 ) is a source gas of considerable interest in plasma research and industry since it is used for the surface modification of steel components in mechanical engineering and automotive industries as well as for plasma etching of semiconductor devices.…”
Section: General Considerationsmentioning
confidence: 99%